Penegakan Hukum Persidangan Cepat Dalam Penyelesaian Perkara Pelanggaran Lalu Lintas (Studi Satlantas Polrestabes Medan) - Foni Mega Wahyuni; Triono Eddy; Alpi Sahari (Mahesa Research Center, 2020)
Procedures for handling cases of traffic violations in Indonesia are regulated by Law Number 22 of 2009 concerning Road Traffic and Transport (LLAJ Law) which is a substitute for Act Number 14 of 1992 concerning Road Traffic and Transportation and Law Number 8 Year 1981 concerning Criminal Procedure Law. In addition, there are several derivative regulations that complement the provisions in the Act. Traffic violations in the Criminal Procedure Act (KUHAP) are grouped together with minor criminal offenses to follow the procedure for examining fast events. The method in this research is empirical juridical legal research type, which is a study that conducts a study of research in the field, conducted a direct research (risearch) regarding the enforcement of court proceedings quickly in the settlement of traffic violation cases. This research uses a qualitative approach. Based on the research, it was found that there were several obstacles in enforcing fast trial law in the settlement of traffic violations, among others: First, the number of traffic violations in Medan City which made the Judges who heard would be overwhelmed, coupled with less extensive room facilities or inadequate infrastructure facilities. which will make the room will be filled with traffic violators who will sit in the courtroom. Second, in the trial process of fast events there are still many traffic violators who use brokers in their law enforcement processes, because the crowds of court officials sometimes find it difficult to distinguish which brokers often play in the maintenance of the law enforcement process.